Vera, Nadezhda, Voina . Vera, Nadezhda, Voina . Faith, Hope, and War . Вера, Надежда, Война - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Members of the Russian part of the Committee for the Control and Inspection in Abkhazia talk about the Georgian-Abkhaz conflict. Featured in the program: Vorob'ev, IUrii (Deputy Chairman of the Russian Search and Rescue Services Council); Gorelov, Gennadii (Member of the Supreme Council of the Russian Federation); Pastukhov, Boris (Deputy Minister of Foreign Affairs of the Russian Federation); Ryklina, Marina (Press Center of the State Committee of Russian Federation for Civil Defense) Члены российской части комиссии по контролю и инспекции в Абхазии рассказывают о ситуации в зоне грузино-абхазского конфликта. В программе участвуют: Воробьев, Юрий (Заместитель председателя ГКЧС России); Горелов, Геннадий (Член Верховного совета Российской Федерации); Пастухов, Борис (Заместитель министра иностранных дел Российской Федерации); Рыклина, Марина (Представительница пресс-центра ГКЧС России)